1975
DOI: 10.2307/589845
|View full text |Cite
|
Sign up to set email alerts
|

Sex Discrimination among University Teachers: A British-American Comparison

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. 26IThis content downloaded from 128.235.251.160 on Sat, 3 Jan 2015 13:56:08 PM All use subject to JSTOR Terms and ConditionsEessa Blackstone e Oliver Fulton Sex discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Nearly twenty years ago, Blackstone and Fulton (1975) presented evidence to demonstrate this in British and American universities, we have shown that women, including those whom, to judge by their research output, it would be insulting to dismiss as lacking motivation or commitment to their work, are not rewarded for their achievements to the same degree as comparable men (p. 269).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly twenty years ago, Blackstone and Fulton (1975) presented evidence to demonstrate this in British and American universities, we have shown that women, including those whom, to judge by their research output, it would be insulting to dismiss as lacking motivation or commitment to their work, are not rewarded for their achievements to the same degree as comparable men (p. 269).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence, notably the small numbers of female applicants for first jobs, with their rate of success about the same as for males (Blackstone & Fulton, 1975), and the relative apparent weakness in the vital respect of publications among the existing women university teachers, suggests that this is not the case--not overtly, at any rate, although some subtler, covert forms of discrimination have been argued. Half a century ago, in discussing Women's Work in Modern England, Brittain (1928) insisted that to gain a university chair, "a women has still[sic] to be considerably better qualified than a man".…”
Section: Opportunities For Women University Teachersmentioning
confidence: 91%
“…But this issue has been a long-standing one, and remains as 'unfinished business' (Ross, 1992). Nearly twenty years ago, Blackstone and Fulton (1975) showed that, 'women, including those whom, to judge by their research output, it would be insulting to dismiss as lacking motivation or commitment to their work, are not rewarded for their achievements to the same degree as comparable men 1 (p.269).…”
mentioning
confidence: 97%